2008
DOI: 10.1021/jm800386y
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin Spindle Protein (KSP) Inhibitors. 9. Discovery of (2S)-4-(2,5-Difluorophenyl)-N-[(3R,4S)-3-fluoro-1-methylpiperidin-4-yl]-2-(hydroxymethyl)-N-methyl-2-phenyl-2,5-dihydro-1H-pyrrole-1-carboxamide (MK-0731) for the Treatment of Taxane-Refractory Cancer

Abstract: Inhibition of kinesin spindle protein (KSP) is a novel mechanism for treatment of cancer with the potential to overcome limitations associated with currently employed cytotoxic agents. Herein, we describe a C2-hydroxymethyl dihydropyrrole KSP inhibitor ( 11) that circumvents hERG channel binding and poor in vivo potency, issues that limited earlier compounds from our program. However, introduction of the C2-hydroxymethyl group caused 11 to be a substrate for cellular efflux by P-glycoprotein (Pgp). Utilizing k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 49 publications
2
87
0
Order By: Relevance
“…Similar to microtubule-targeted drugs, Eg5 inhibition leads to mitotic arrest and cell death (10,11). The chemical structure of K858 is different from many previously identified Eg5 inhibitors (9)(10)(11)(12)(13)(14)(15)(16), and our data indicate that it preferentially exerts antitumor effects while preserving normal cells, thus potentially inducing fewer adverse events. In support of this, K858 had no effect on microtubule organization and did not induce DNA damage, aberrant chromosome segregation, or aneuploid formation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Similar to microtubule-targeted drugs, Eg5 inhibition leads to mitotic arrest and cell death (10,11). The chemical structure of K858 is different from many previously identified Eg5 inhibitors (9)(10)(11)(12)(13)(14)(15)(16), and our data indicate that it preferentially exerts antitumor effects while preserving normal cells, thus potentially inducing fewer adverse events. In support of this, K858 had no effect on microtubule organization and did not induce DNA damage, aberrant chromosome segregation, or aneuploid formation.…”
Section: Discussionmentioning
confidence: 66%
“…In particular, Eg5, a key molecule involved in the formation of bipolar spindles (8), is one of the most attractive target enzymes in antimitotic drug discovery, and several chemotypes of small molecule Eg5 inhibitors have been reported (9)(10)(11)(12)(13)(14)(15)(16). The Eg5 inhibitors S-trityl-L-cystein (10), CK0106023 (11), ispinesib (12), KSP-IA (13), and MK-0731 (14) were identified in a biochemical screen for inhibitors of the ATPase activity of Eg5. Monastrol (15) and HR22C16 (16) were selected using a phenotypebased screen for antimitotic agents and were subsequently identified as Eg5 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Several inhibitors of KSP have progressed into clinical trials and many others are in preclinical development. [30][31][32] Similarly, PLK1 inhibitors have moved into clinical studies in patients with locally advanced or metastatic cancers, 33 and in vitro studies have shown that the combination of PLK1-specific siRNAs with modern breast cancer drugs could represent rational combinations to improve the sensitivity in a synergistic manner. 34 Using luciferase as a biomarker, we first showed in vitro and in vivo KD (in tumor tissue) of luminescence (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
“…The benzyl group occupies a hydrophobic pocket bounded by Trp 127, Pro 137, Val 210 and Tyr 211, and is further enclosed by the benzamide moiety of ispinesib, with which it forms an intramolecular edgeto-face stacking interaction. The isopropyl group lies in a small hydrophobic patch between the backbones of Leu 214/Glu215 and Tyr 211, while the quinazolinone core is situated in deeper hydrophobic pocket formed by Ile 136, Leu160, Leu171, [ 13 ]; ( b ) MK0731 binding to Eg5 (PDB entry 3CJO) [ 25 ]; ( c ) EMD534085 binding to Eg5 (PDB entry 3L9H) [ 26 ]; ( d ) STLC binding to Eg5 (PDB entry 3KEN) [ 27 ]. The ligands are coloured by atom type: green (C), cyan (F), dark green (Cl), yellow (S), blue (N) and red (O).…”
Section: Ispinesibmentioning
confidence: 99%
“…While working to overcome limitations in in vivo effi cacy and affi nity for the hERG channel, the researchers at Merck revisited the simpler dihydropyrrole scaffold of 3.13 (Table 2.1 ) [ 25 ]. During lead optimisation, they had noted that a hydroxymethyl substituent was a viable alternative to the solubilising propylamine side chain introduced later in the program which did not display the increased propensity for hERG channel interactions.…”
Section: Development Of the C-2 Hydroxymethyl Dihydropyrrole Seriesmentioning
confidence: 99%